The relationship between starch structure and digestibility by time-course digestion of amylopectin-only and amylose-only barley starches. (May 2023) - Liang, Wenxin; Ding, Li; Guo, Ke; Liu, Yang; Wen, Xiaoxia; Kirkensgaard, Jacob Judas Kain; Khakimov, Bekzod; Enemark-Rasmussen, Kasper; Henrik Hebelstrup, Kim; Herburger, Klaus; Liu, Xingxun; Persson, Staffan; et al.
Abstract: The multi-scale structural dynamics of amylopectin-only barley starch (APBS), normal barley starch (NBS), and amylose-only barley starch (AMBS) digested with amylolytic enzymes for 120 min were investigated in this study. For all starches, 0–20 min was identified as a rapid digestion stage, followed by a 20–120 min slow digestion. For APBS and NBS, the content of short chains (DP ≤ 12) and the thickness of crystalline and amorphous nano-lamellae increased, whereas the crystallinity decreased, and pores were generated on the granular surface during the rapid digestion stage. At the following slow digestion stage, the branching degree and relative amount of double helices increased, the crystalline and lamellar structures were lost, and the hydrolyzed starch segments aggregated. For AMBS, the rapid digestion stage was characterized by an increased content of short chains (DP ≤ 8) and B-type crystals and decreased amounts of V-type crystals. Furthermore, the lamellar and granular structures were lost, and digestion residues aggregated during the first stage of AMBS, which were formed in the second digestion stage of APBS and NBS. The second slow digestion stage of AMBS was characterized by an increased branching degree and a decreased relative content of single helices. It is suggested that the aggregated digestion residues at the initial digestion stage are the main reason for the overall low digestibility of AMBS. Graphical abstract: Image 1 Highlights: Amylose barley starch (AMBS) lost granular structure at initial digestion stage. AMBS reorganized immediately and was thereafter hydrolytic resistant. Single helices and the V-type crystals decreased in AMBS upon hydrolysis. Amylopectin barley starch (APBS) first generated pores and then reorganized. APBS had a high content of double helices after digestion.